The Activities of the Association “Centre Volunteers of Suffering” of the Archdiocese of Warmia - Bielinowicz, Adam (Studia Warmińskie, 2014)
The article presents the activities of the association the Centre of Volunteers of Suffering in the Archdiocese of Warmia, its pastoral goals, and objectives. Moreover, the author discusses the spirituality of the community and includes a biographical sketch of the founder of the association – the Servant of God, Fr. Monsignor Luigi Novarese, whose beatification took place on 11 May 2013.